Protein kinase D1 mRna level may predict cancer-specific survival in heavy smokers with esophageal squamous cell cancers. Issue 2 (1st March 2014) - Xie, X.; Zhang, S.-S.; Wen, J.; Yang, H.; Luo, K.-J.; Yang, F.; Hu, Y.; Fu, J.-H.
Summary: Protein kinase D 1 (PRKD 1) is a kinase that regulates various pathways, which involve in cell proliferation, apoptosis, cell adhesion and invasion. Although PRKD 1 expression has been observed in many cancers, its role in esophageal squamous cell cancer (ESCC ) has not been well reported. As its dysregulation in cancers is organ specific, we sought to investigate the potential role of PRKD 1 in the progression of ESCC . Samples were collected from 178 patients with completely resected ESCCs at S un Y at-sen U niversity C ancer C enter, including 47 pairs of tumorous and non-tumorous tissues. PRKD 1 mRNA expression was investigated by quantitative real-time polymerase chain reaction. Receiver operating characteristic (ROC ) curve analysis was used to search for a feasible cut-off point of PRKD 1 mRNA levels for predicting cancer-specific survival. K aplan–M eier and multivariate C ox regression analysis were used to assess the prognostic value of PRKD 1 mRNA level in ESCC patients. In result, upregulation of PRKD 1 mRNA was detected in 55.3% (26/47) of ESCC tissues compared with paired non-tumorous ones ( P = 0.011). ROC analysis indicated 3.28 as a cut-off point, and thus 72 and 106 tumors with low and high PRKD 1 mRNA expression were categorized. High-PRKD 1 mRNA expression in tumors appeared with more frequency in heavy smokers ( P = 0.002) and patients with advanced pathological T category ( P = 0.034). K aplan–M eier analysis indicated that patients with low-PRKD 1 mRNA had a longer cancer-specific survival than the ones with high-PRKD 1 level ( P = 0.044). Multivariate analysis showed that tumorous PRKD 1 mRNA expression was an independent prognostic factor (hazard ratio: 1.538, 95% confidence interval: 1.018–2.323, P = 0.041) in resected ESCC . Subgroup analysis revealed that the discernibility of PRKD 1 mRNA level on ESCC outcomes was only pronounced in heavy smokers ( P = 0.002), but not in non-heavy smokers ( P = 0.870). PRKD 1 might play a potential oncogenic role in ESCC . It might be an independent biomarker to predict prognosis in heavy smokers with ESCC .